2021
DOI: 10.1002/chem.202100029
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity in the Ligand Functionalization of Photocatalytic Metal Oxide Nanoparticles for Phase Transfer and Self‐Assembly Applications

Abstract: The functionalization of photocatalytic metal oxide nanoparticles of TiO 2 , ZnO, WO 3 and CuO with amineterminated (oleylamine) and thiol-terminated (dodecane-1thiol) alkyl-chain ligands was studied under ambient conditions. A high selectivity was observed in the binding specificity of a ligand towards nanoparticles of these different oxides. It was observed that oleylamine binds stably to only TiO 2 and WO 3 , whereas dodecane-1-thiol binds stably only to ZnO and CuO. Similarly, polar-to-nonpolar solvent pha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 67 publications
0
17
0
Order By: Relevance
“…When plasmonic nanostructures are arranged periodically, electrodynamic coupling of the nanostructures enhances the light-matter interaction as compared to isolated nanostructures 1 , 2 . Thus, periodic arrays of nanostructures have gained increasing attention in recent years for the application in light driven processes such as solar energy harvesting 3 , photovoltaics 4 , photocatalysis 5 , 6 , SERS (surface-enhanced Raman spectroscopy) 7 , fluorescence 8 , SEIRA (surface-enhanced infrared absorption spectroscopy) 9 , sensing 10 , photoemission and photodetection 11 , etc. The plasmonic enhancement of these various processes can occur through different mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…When plasmonic nanostructures are arranged periodically, electrodynamic coupling of the nanostructures enhances the light-matter interaction as compared to isolated nanostructures 1 , 2 . Thus, periodic arrays of nanostructures have gained increasing attention in recent years for the application in light driven processes such as solar energy harvesting 3 , photovoltaics 4 , photocatalysis 5 , 6 , SERS (surface-enhanced Raman spectroscopy) 7 , fluorescence 8 , SEIRA (surface-enhanced infrared absorption spectroscopy) 9 , sensing 10 , photoemission and photodetection 11 , etc. The plasmonic enhancement of these various processes can occur through different mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…[ 8 ] Particle extraction through liquid–liquid interface for colloidal processing of ZnO particles was also performed with the use of octanohydroxamic acid and bufexamac as extractors. [ 9 ] Lenaerts et al [ 10 ] found that a polar‐to‐nonpolar solvent phase transfer of TiO 2 and WO 3 nanoparticles could be achieved by using oleylamine, but not dodecane‐1‐thiol, whereas the opposite holds for ZnO and CuO. In contrast to most phase transfer agents in use, polysorbate 80 is a synthetic nonionic surfactant of highly proven safety, which makes it useful for drug formulation.…”
Section: Introductionmentioning
confidence: 99%
“…The particle size distribution for specific values of μ and σ was obtained by the iterative procedure. The number of particles, NTotal had to be first estimated with different values until the total number of atoms calculated from the entire distribution of nanoparticles with the given μ and σ results in 1.5055 x 10 19 . The molar mass and density values used in the calculations were 107.9 gm/mole and 10.5 gm/cm 3 .…”
Section: Mie Analytical Solution For a Distribution Of Nanoparticlesmentioning
confidence: 99%
“…[15][16] Thus, the minimization of the polydispersity is one of the important challenges of this synthesis route as highly polydisperse or irregular particles poses difficulties for further applications. [17][18] [19] It is widely believed and accepted that the optical properties of plasmonic nanoparticles strongly depend on the size, polydispersity and nonuniformity of the particle morphology. [20][21] [22] [23]It has also been shown that polydispersity has a strong effect on the total energy absorption and thus, on the plasmonic heat generation.…”
Section: Introductionmentioning
confidence: 99%